The Calculus Concept Inventory Applied to the Case of Large Groups of Differential Calculus in the Context of the Program “Ser Pilo Paga” in Colombia. (2020)
The Calculus Concept Inventory (CCI), Epstein (2013) aims to test the understanding of calculus ideas, rather than ability to perform calculations. In this paper the CCI is used to measure the effect of the undergraduate calculus cohort over the understanding of calculus in a heterogeneous population including recipients of the program Ser Pilo Paga (Pilos). There is a global positive gain of 0.10 (3), a weak correlation between gain and the percentage of Pilos, a negative correlation between initial score and the gain, and no correlation between class size and gain. The values hopefully would provide a baseline for comparing future interventions on the teaching of calculus.